2007
DOI: 10.1103/physrevb.76.085112
|View full text |Cite
|
Sign up to set email alerts
|

Metallic phase in the two-dimensional ionic Hubbard model

Abstract: We investigate the phases of the ionic Hubbard model in a two-dimensional square lattice using determinant quantum Monte Carlo (DQMC). At half-filling, when the interaction strength or the staggered potential dominate we find Mott and band insulators, respectively. When these two energies are of the same order we find a metallic region. Charge and magnetic structure factors demonstrate the presence of antiferromagnetism only in the Mott region, although the externally imposed density modulation is present ever… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 31 publications
(41 reference statements)
8
85
5
Order By: Relevance
“…The ionic-Hubbard model has been studied extensively in one dimension [21], and two dimensions, and the nature of interim phase has been debated [22]. In addition to various low-dimensional techniques employed to study such model, the DMFT technique has also been employed to study the nature of intermediate phase of this model for metallic parent systems [9,23].…”
Section: Introductionmentioning
confidence: 99%
“…The ionic-Hubbard model has been studied extensively in one dimension [21], and two dimensions, and the nature of interim phase has been debated [22]. In addition to various low-dimensional techniques employed to study such model, the DMFT technique has also been employed to study the nature of intermediate phase of this model for metallic parent systems [9,23].…”
Section: Introductionmentioning
confidence: 99%
“…21,22 These studies all suggested that a phase with nonzero spectral weight at the Fermi energy exists between the band insulator and Mott insulator phases, at least in some of the phase diagram. However, there has been some debate over whether this phase is metallic 21,22 or bond ordered. 20 There has been far less work on the ionic Hubbard model away from half-filling.…”
Section: A Previous Theories Of the Ionic Hubbard Modelmentioning
confidence: 99%
“…This model has been studied using both cluster DMFT 20 and determinant quantum Monte Carlo ͑DQMC͒. 21,22 These studies all suggested that a phase with nonzero spectral weight at the Fermi energy exists between the band insulator and Mott insulator phases, at least in some of the phase diagram. However, there has been some debate over whether this phase is metallic 21,22 or bond ordered.…”
Section: A Previous Theories Of the Ionic Hubbard Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The ionic Hubbard model on half-filled bipartite lattices has attracted interest because it undergoes a transition from a Mott insulator to a band insulator. [12][13][14][15][16][17][18] Furthermore, away from halffilling and on frustrated lattices the ionic Hubbard model shows a subtle interplay between charge and spin ordering and metallic and insulating phases. [19][20][21][22][23][24] The Hamiltonian of the ionic Hubbard model is…”
Section: Introductionmentioning
confidence: 99%